P115 A tale of two networks: a simultaneous Fmri-tDCS study of anodal versus cathodal stimulation. Issue 3 (March 2017) - Li, L.; Violante, I.; Ross, E.; Leech, R.; Hampshire, A.; Carmichael, D.; Sharp, D.
Abstract : Introduction: The right inferior frontal gyrus (rIFG) is important in co-ordinating changes in network activity, which underlie normal cognitive control (Hampshire, 2015 ). TDCS can modulate cognition, though little is known about its neurophysiological effects. Objectives: To investigate the neurophysiological effects of rIFG (F8) anodal (a-tDCS) and cathodal (c-tDCS) tDCS. Materials & methods: 26 controls participated in a novel simultaneous fMRI/tDCS study. Subjects performed a blocked Choice Reaction Time task (CRT) (fixation cross between task blocks) and had 3 types of tDCS (1.8mA: a-tDCS, c-tDCS or sham), giving 6 possible combinations (Fig. 1) . Subjects then performed 3 runs of a Stop Signal Task (SST), an inhibitory control task requiring subjects to withhold an automatic response when an infrequent 'Stop' signal appears. Each run had sham, a-tDCS or c-tDCS (2mA), in a counterbalanced order across participants. FMRI was analysed in the FMRIB FSL package. Results: CRT performance activated the Dorsal Attention Network, sensorimotor and primary visual areas and deactivated the Default Mode Network (DMN), as seen in (Sharp, 2011 ) (Fig. 2A). The effect of tDCS depends on: 1.  Brain state: tDCS/fixation and tDCS/task had opposing effects on DMN and task network activity (Fig. 2B ) 2.  Electrode polarity: c-tDCS/CRT produced greater activation within task regions and deactivation of DMN regions than a-tDCS/CRT (Fig. 2C). Inhibiting a response in the SST led to expected DMN deactivation (Aron, 2006 ). Compared to sham tDCS, when inhibiting a response, c-tDCS resulted in: A failure to deactivate the medial frontal cortex, a key DMN node ( p  = 0.03). Increased activation of a right frontal-subthalamic network important in inhibitory control (Bonnelle, 2012 )( p  = 0.02). Conclusions: Short periods of tDCS can modulate brain network activity. The neurophysiological effect of tDCS is strongly dependent on underlying brain state. C-tDCS and a-tDCS have distinct effects on brain network activity.